The first English language teachers of the nineteenth century - Santos, Elaine Maria (2021)
The main objective of this article is to relate the trajectory of three 19th century English language teachers to the process of institutionalizing English language teaching, in the face of French hegemony. To this end, the assumptions of the New Cultural History were used, favoring different sources, such as official documents, 19th century newspapers and prefaces of the compendiums published by the selected teachers. The research findings show us that the struggles faced by teachers were of great importance for the consolidation of a field of work at different times of the 19th century, taking into account that French played a hegemonic role with regard to language teaching.